The Relationship between Children’s Developmental Functioning and Participation in Social Activities in Portuguese Inclusive Preschool Settings - Coelho, Vera; Pinto, Ana Isabel (Frontiers in Education, 2018)
In Portugal, substantial changes occurred in early childhood intervention and special education with the Decree-Law 3/2008. This legislation stresses the importance of a multidimensional approach to assessment-intervention processes, setting the International Classification of Functioning Disability and Health (ICF) as a critical tool in determining children’s functioning and participation. To establish criteria for eligibility and defining the standard for developing assessment-intervention procedures in accordance with the ICF model, became topics of great relevance for researchers, practitioners and policy-makers. Assuming that young children develop through proximal processes, such as playing and interacting with adults/peers/materials, their participation in everyday environments becomes a crucial outcome regarding learning and development, as highlighted by the ICF conceptual model. Children’s participation can be defined as encompassing two dimensions: frequency of activities attended by children, and their level of engagement. This observational study analyzes engagement and time spent in activities with different levels of social complexity, in children with heterogeneous developmental functioning (DF). By focusing on different levels of DF we aim to explore how functionality measures based on ICF can be useful to characterize all children, thus ensuring an inclusive assessment. Participants were 247 preschool-aged children: 54 with disabilities (low DF), 78 at-risk (medium-low DF); 115 with typical development (high DF). DF was assessed by a short-version of the Matrix for Assessment of Activities and Participation. Engagement and time in activities were observed with the Child Observation in Preschool. Analyses of Variance were conducted to explore differences between the three groups of children. The three DF groups differed significantly on the proportion of time spent in activities with different levels of social complexity. Children with disabilities spent less time in cooperative and social play (activities with higher social complexity) and their levels of engagement were significantly lower than the other groups, both for more and less complex activities. Discussion focuses on assessment demands posed by legislation and the ICF model, highlights the need to ensure all children’s participation in different everyday activities, and underlines the role of environmental adjustments for children with disabilities and at risk to guarantee their right to fully participate in inclusive settings.